POVERTY IN UPPER WEST REGION OF GHANA: DETERMINANTS AND POLICY PRESCRIPTIONS - Ibrahim, M.; Sare, Y. A.; Adam, R. (UDS International Journal of Development, 2019)
This study examines the factors influencing monetary and non–monetary poverty in Upper West Region of Ghana. The authors relied on primary data collected using a questionnaire from 395 households to construct a multidimensional non–monetary measure of poverty using the Multiple Correspondence Analysis (MCA) while invoking instrumental variables estimation approaches that deal with potential endogeneity eminent in poverty studies. The results reveal varying determinants of both measures of poverty. The findings indicate that, gender matters more for non–monetary poverty than monetary poverty while household size and educational level robustly influences only monetary poverty. Age weakly affects only non–monetary poverty albeit in a non–linear fashion. Access to microcredit, savings and gainful employment individually reduces household poverty while improving welfare. Job insecurity accelerates poverty irrespective of the measure while remittance and financial inclusion are exceedingly crucial for only non–monetary poverty. Although crop loss and idiosyncratic risks increase household poverty, they mean less for non–monetary poverty. In addition to finding weak impact of government social protection programmes on poverty, we also do not find any dampening effect of such programmes on household shocks. To the extent that households are exposed to spatial and idiosyncratic shocks in the face of weak protection programmes, we call for a new broad set of policies and safety nets capable of insulating households against these vagaries. Keywords: Monetary poverty, non-monetary poverty, shocks, IV-probit, Wa